Modulation of peripheral blood immune cells by early use of steroids and its association with clinical outcomes in patients with metastatic non-small cell lung cancer treated with immune checkpoint inhibitors. Issue 1 (27th February 2019) - Fucà, Giovanni; Galli, Giulia; Poggi, Marta; Lo Russo, Giuseppe; Proto, Claudia; Imbimbo, Martina; Ferrara, Roberto; Zilembo, Nicoletta; Ganzinelli, Monica; Sica, Antonio; Torri, Valter; Colombo, Mario Paolo; et al.
Abstract : Background: Steroids are frequently used in patients with metastatic non-small cell lung cancer (mNSCLC), but they could be detrimental for patients treated with immune checkpoint inhibitors (ICIs). Here, we assessed the association between early use of steroids, clinical outcomes and peripheral immune blood cells modulation in patients with mNSCLC treated with ICIs. Methods: We reviewed patients with mNSCLC treated at our institution between April 2013 and December 2017. Early use of steroids was defined as the use of a daily prednisone-equivalent dose ≥10 mg for at least 1 day within 28 days after ICI initiation. Peripheral immune blood cell counts were retrieved at baseline and at 4 and 6 weeks after ICI initiation. Results: Out of 151 patients included, 35 (23%) made early use of steroids that was associated with poor disease control (OR 0.32, p=0.006), progression-free survival (HR 1.80, p=0.003) and overall survival (HR 2.60, p<0.001). Early use of steroids significantly correlated with higher median absolute neutrophil count, neutrophil to lymphocyte ratio (NLR) and derived NLR, and lower median absolute and relative eosinophil count, both at 4 and 6 weeks after ICI initiation. Conclusions: In patients with mNSCLC treated with ICIs, early use of steroids was associated with worse clinical outcomes and remarkable modulation of peripheral blood immune cells, which could contribute to restraining the activation of antitumour immunity. If confirmed in prospective studies, these findings would highlight the importance of carefully evaluating and, whenever possible, avoiding steroids during early phases of ICI treatment.